Genista sessilifolia DC. extracts induce apoptosis across a range of cancer cell lines. (19th March 2013) - Bontempo, P.; Rigano, D.; Doto, A.; Formisano, C.; Conte, M.; Nebbioso, A.; Carafa, V.; Caserta, G.; Sica, V.; Molinari, A. M.; Altucci, L.
Abstract: Objectives: Restorative properties of medicinal plants such as Genista sessilifolia DC. have often been suggested to occur, in epidemiological studies. However, full characterization of effective principles responsible for this action has never previously been performed. Here, we have characterized G. sessilifolia 's anti‐cancer effects and identified the chemical components involved in this anti‐tumour action. Materials and methods: Cell cycle, apoptosis, necrosis, differentiation analyses, high‐performance liquid chromatography, western blotting, RNA extraction, real‐time PCR and primers have all been observed/used in the study. Results: We report that G. sessilifolia methanol extract has anti‐cancer activity on solid and haematological cancer cells. G. sessilifolia extract's anti‐proliferative action is closely bound to induction of apoptosis, whereas differentiation is only weakly modulated. Analysis of G. sessilifolia extract, by high‐performance liquid chromatography, identifies fraction 18–22 as the pertinent component for induction of apoptosis, whereas fractions 11–13 and 27–30 both seem to contribute to differentiation. G. sessilifolia extract induces apoptosis mediated by caspase activation and p21, Rb, p53, Bcl2‐associated agonist of cell death (BAD), tumour necrosis factor receptor super‐family, member 10 (TRAIL) overexpression and death receptor 5 (DR5). Accordingly, fraction 18–22 inducing apoptosis was able to induce TRAIL. Conclusions: Our results indicate that G. sessilifolia extract and its fraction 18–22 containing genistin and isoprunetin, were able to induce anti‐cancer effects supporting the hypothesis of a pro‐apoptotic intrinsic content of this natural medicinal plant.